1973
DOI: 10.4315/0022-2747-36.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Counts of Individual Producer and Commingled Grade a Raw Milk1

Abstract: Microbial populations of Grade A raw milk samples from 105 individual producers and 74 bulk tank trucks (commingled) were enumerated by Standard Plate Count (SPC), psychrotrophic count (PBC), coliform count (CC), laboratory pasteurized count (LPC), thermophilic count (TBC), yeast and mold count (Y&M), and special penicillin (PEN) and crystal violet tetrazolium (CVT) agar count procedures. In addition, microbial populations were determined by the SPC, PBC, PEN, and CVT procedures after preliminary incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Generally, the yeast cells are found in both raw and pasteurised milk (Foster et al 1957;Randolph et al 1973;JONES and LANGLOIS, 1977;Fleet and Mian, 1987) but at a low population mostly 10 3 cells /mL (Fröhlich-Wyder, 2003), while in the present study the input parameters of plasma bubbling treated sample markedly affect the decontamination of yeast cells which indicates a good finding.…”
Section: Yeast and Mouldsupporting
confidence: 59%
See 1 more Smart Citation
“…Generally, the yeast cells are found in both raw and pasteurised milk (Foster et al 1957;Randolph et al 1973;JONES and LANGLOIS, 1977;Fleet and Mian, 1987) but at a low population mostly 10 3 cells /mL (Fröhlich-Wyder, 2003), while in the present study the input parameters of plasma bubbling treated sample markedly affect the decontamination of yeast cells which indicates a good finding.…”
Section: Yeast and Mouldsupporting
confidence: 59%
“…This observation for yeast cells could be due to a different kind of stress produced by the cold plasma generation such as reactive oxygen and nitrogen species which are responsible for the damage of cellular components of yeast cells, as a result, cell death was observed (Polčic and Machala, 2021). Generally, the yeast cells are found in both raw and pasteurised milk (Foster et al 1957;Randolph et al 1973;JONES and LANGLOIS, 1977;Fleet and Mian, 1987) but at a low population mostly 10 3 cells /mL (Fröhlich-Wyder, 2003), while in the present study the input parameters of plasma bubbling treated sample markedly affect the decontamination of yeast cells which indicates a good finding.…”
Section: Yeast and Mouldmentioning
confidence: 99%
“…Often, information on yeasts is reported as an appendage to more detailed bacteriological studies. Generally, the available information shows that yeasts occur in both raw (Foster et al 1957;Ingram 1958;Randolph et al 1973;Engel 1986a) and pasteurized (Jones & Langlois 1977;Fleet & Mian 1987;Vadillo et al 1987) milks, but at low, insignificant populations. Populations less than lo3 cells/ml are mostly reported but, occasionally, counts as high as lo4 cells/ml can occur.…”
Section: Milkmentioning
confidence: 99%
“…Yeasts are commercially significant in foods because they cause spoilage or conduct desirable fermentations (Rose & Harrison 1970;Reed & Peppler 1973). Infections arising from the few, known pathogenic yeasts, such as Candida albicans or Cryptococcus neoforrnans (Hurley et al, 1987) are not transmitted through foods.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the acceptable range of coliform in milk is 0-1000/ mL at 24h with 37°C (‘FSHN 312: Applied Microbiology’, 2018) which was owned by the plasma bubbling treated sample M3. Previously it has been observed that the yeast cells are found in both raw and pasteurised milk (Foster et al ., 1957)(Randolph et al ., 1973)(JONES and LANGLOIS, 1977)(Fleet and Mian, 1987) but at a low population mostly 10 3 cells /mL (Fröhlich-Wyder, 2003), while in this study at M3 treated sample yeast cells were not observed which indicates a good finding.…”
Section: Resultsmentioning
confidence: 99%